Analysis of the Financial Performance of the Jambi City Government Using Variance Analysis for the 2020-2022 Fiscal Year - Utami, Endang Surahyani; Iskandar Sam; Salman Jumaili (Indonesian Journal of Economic & Management Sciences, 2024)
This research aims to evaluate the Financial Performance of the Jambi City Government through Variance Analysis for the 2020-2022 budget year. This research uses a qualitative descriptive approach by utilizing secondary data originating from the Jambi City Revenue and Expenditure Budget Realization Report for the same period. The findings show that the Financial Performance of the Jambi City Government as assessed through Income Variance Analysis is classified as Poor, Income Growth is identified as positive, the Degree of Decentralization is classified as Sufficient, the Regional Financial Dependency Ratio is classified as Very High, the Regional Financial Independence Ratio is classified as Low, the PAD Effectiveness Ratio is considered to be Fairly Effective. In terms of Performance Expenditure Variance Analysis, it is rated as Good, Operational Expenditure Analysis is rated as Fairly Good, Capital Expenditure Analysis is also rated as Fairly Good, and the Regional Expenditure Efficiency Ratio is classified as Efficient